Pengaruh Kelengkapan Resep Terhadap Prescribing Error Obat Golongan Benzodiazepin di Tiga Apotek Kota Bandung - Nuke Fendiana; Meta Kartika Untari; Ika Purwidyaningrum (Journal Syifa Sciences and Clinical Research, 2022)
Reviewing prescriptions, especially psychotropic drugs, is one part of clinical pharmacy services carried out by pharmacists to analyze drug-related problems and avoid medication errors, especially at the prescribing stage. The purpose of this study was to determine the suitability of prescribing services for benzodiazepine drugs with the Regulation of the Minister of Health of the Republic of Indonesia and to find the effect of administrative, pharmaceutical and clinical completeness on the incidence of prescribing errors in prescribing benzodiazepine drugs in three pharmacies in Bandung City in 2021. This research method is a descriptive research conducted retrospectively where the data were prescriptions for January 2021-December 2021 at three Bandung City Pharmacies. The analysis was carried out by grouping each data variable from administrative, pharmaceutical and clinical aspects which were then processed using Microsoft Excel and SPSS programs. The results showed that the completeness of prescription psychotropic benzodiazepines still did not meet the requirements of the Regulation of the Minister of Health of the Republic of Indonesia No. 73 of 2016 where the total incidence of prescribing errors in the prescription section was 11.66%, subscription was 16.58% and pro was 100. %, there is a significant relationship with a correlation coefficient value of 0.269 which means that there is a sufficient influence between doctor qualifications and the incidence of prescribing errors and there is a relationship between the completeness of administrative, pharmaceutical and clinical prescriptions with the incidence of prescribing errors which is significant with a probability value of 0.000 and a correlation coefficient value of 0.749 which means strong influence. Based on the data above, it can be concluded that the completeness of prescriptions in the Administrative, Pharmaceutical and Clinical categories is still not complete in accordance with the Regulation of the Minister of Health No. 73 of 2016.